Comparison of different measures for the single point uncertainty in industrial X-ray computed tomography - Müller, Andreas; Hausotte, Tino (9th Conference on Industrial Computed Tomography, 2019)
The concept of single point uncertainty describes a methodology to statistically evaluate the local measurement results of a measurement series with respect to the associated reference geometry. The single point uncertainties can be used as local quality parameters or weighting factors in subsequent processing of a measurement and can therefore have a significant impact on the final measurement results. The core routine used in former work at the Institute of Manufacturing Metrology, which is based on ray-triangle intersection tests, provided accurate results under most conditions. Nevertheless, some disadvantages were observed, including the very high computational demand and an inaccurate sampling of edge regions. In order to compensate for these deficiencies, another distance measure utilizing an expanded nearest neighbour approach was implemented and compared to the existing solution. It could be shown that the alternative solution for the determination of the single point uncertainty in repeated computed tomography (CT) measurements can provide very similar results while having substantially less computational requirements on the hardware used.<br
Keywords: dimensional metrology; single point uncertainty; ray tracing; GPGPU